20 Developing symptom control guidance for COVID-19 patients who are deteriorating despite non-invasive ventilation (NIV) as their ceiling of treatment. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Evans, Lowri; Atkinson, Clea; Byrne, Anthony
Abstract : Background: COVID-19 positive patients often develop Type 1 respiratory failure requiring CPAP, meaning deteriorating patients are often alert, leading to a challenging end of life situation at the time of NIV discontinuation. The Palliative Care team were asked to help better manage symptoms for COVID-19 positive patients approaching the end of life, and specifically those patients having NIV support as their ceiling of treatment, who were deteriorating very rapidly despite this. Methods: A case note review was performed. Guidance was developed following rapid review of existing published guidance for NIV withdrawal and sedation for other comparable clinical situations, with adaptation using the experiential knowledge of the palliative care and respiratory teams in managing COVID-19 positive patients. Finally, to evaluate the guideline an online survey was distributed to respiratory ward staff following the 'first wave'. Results: A symptom control flowchart was developed and agreed for use in the health board specifically for managing the rapidly deteriorating patient with COVID-19 on NIV as their ceiling of treatment. This later formed part of the All Wales COVID-19 National Secondary Care Guidance website. The online survey drew 12 respondents. Following introduction of the guideline the proportion of respondents who felt symptoms were adequately controlled rose from 17% to 58%. Qualitative feedback demonstrated that despite the difficult circumstances, patients were treated with compassion and overall better symptom control was achieved. 91% of relevant staff felt comfortable with the medication doses recommended for symptom control. Conclusions: Key to the appropriate implementation of this guidance has been the support of the local palliative care team and a good working relationship with the respiratory teams. A collaborative approach facilitated the rapid development of guidance in response to a direct patient need. This flowchart has given the respiratory team guidance to support better end of life care and reduce distress for patients, families and staff.